Reparative radiological changes of hip joint after TNF inhibitors in ankylosing spondylitis - Kaouther Maatallah; Ines Mahmoud; Safa Belghali; Kawther Ben Abdelghani; Olfa Saidane; Elyes Bouajina; Ahmed Laatar; Rawdha Tekaya; Leila Abdelmoula (Babol University of Medical Sciences, 2018)
Background: Hip involvement in ankylosing spondylitis (AS) is a common extraspinal arthritic manifestation, which is associated to a worse functional outcome. Little data are available on the effectiveness of conservative treatment strategies. The TNF inhibitors have been proven effective on AS activity parameters. Their structural effect on hip disease however, little is studied. Case presentation: We describe four new cases of reparative changes of a damaged hip joint after treatment with TNF inhibitors. The average of age was 32.5 (27- 36) years. There were 3 men and 1 woman. Hip involvement was bilateral in all cases. Etanercept was prescribed in 3 cases and infliximab in 1 case. At baseline, all patients had a painful and limited hip with high disease activity and an important functional impairment. After an average of 5.5 years of treatment with TNF inhibitors, the BASRI hip evaluated in antero-posterior x-rays of the pelvis remained unchanged at 2.4. The average of mean hip joint space was 2.9mm (2.3-3.6). A widening in hip joint space was observed in all cases with less subchondral cysts. Conclusion: TNF inhibitors seem to be effective on hip joint disease in patients with AS.